Estimation of carbon sequestration rate between linear and curvilinear design landscape setting urban park - Othman, Rashidi; Suid, Suhaili; Hashim, Khairusy Syakirin Has-Yun; Hj. Baharuddin, Zainul Mukrim (2018)
Urban parks are emerging as one of the important spaces in the urban fabric. Urban parks act as places that could increase the tranquillity and comfort of urban life by providing a space for people to relax their mind and become places for recreation and leisure. The need for urban parks became greater as cities expanded and the urban population rapidly grew. Therefore, having an urban park can facilitate a reduction in GHG emissions by alleviating some of the impacts of this dense development. Trees in the urban parks are an important agent to reduce the amount of carbon dioxide accumulate in the urban area. The carbon sequestration rate was calculated by biomass equations, using field data collection, measurement and survey data analysis. This study aimed to calculate, predict and compare carbon sequestration rate produced by plant materials through linear and curvilinear design landscape setting. The decisive outcomes of this study are the optimization of carbon sequestration rate by selecting the right plant material specifications with suitable landscape design setting. The findings revealed that curvilinear design landscape setting sequesters more carbon than linear design landscape setting. Plants with bigger girth and larger quantities sequester more carbon compared to smaller girth and fewer trees. These findings will become a green practice approached towards building a sustainable environment with better design solutions.